Sustainable city development challenged by extreme weather in a warming world - Changjia Li; Tong Lu; Bojie Fu; Shuai Wang; Joseph Holden (Geography and Sustainability, 2022)
The year of 2021 has witnessed many extreme weather events across the world that have shocked and challenged human society, in particular for the populous cities, challenging progress on sustainable city development. In the comment we highlighted the record-breaking rainstorm that is considered to happen only “once-in-a-thousand-years” on 20 July 2021 in Zhengzhou, China; and a series of short and long-term resilience enhancement and risk reducing measures to climate change and natural hazard risks. We found that increasing frequency and intensity of extreme weather events caused by human-induced climate change challenges progress on sustainable city development, but could also accelerate activities to enable cities to become more resilient. This comment is essential to advance towards the sustainable city development goal (SDG 11) in China's mega cities, as well as informing progress for other global cities.